2017
DOI: 10.1186/s12302-017-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

Metazachlor traces in the main drinking water reservoir in Luxembourg: a scientific and political discussion

Abstract: This discussion is centralized around an incident that took place in the Belgian village Witry the 17th of September 2014. A tractor accident led to the discharge of an aqueous solution of the herbicide metazachlor into the creek Moyémont that further merges into the river Sûre. About 20 km downstream, these waters supply the lake of the Upper-Sûre in Luxembourg, the biggest artificial lake and the main drinking water reservoir in the country. The evolution of the concentration of metazachlor and its metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…Luxembourg has vineyards lining the Moselle River, agricultural activity in the north of the country, and a population largely centered in the capital, which together brings in a significant and varied chemical load into the environment. Previous studies have reported the presence of analgesics, antimicrobials, and estrogens in Luxembourgish surface water. Aside from providing data on the level of xenobiotics in Luxembourgish waters, these studies have also demonstrated that the presence of these chemicals is due to inputs from land use, accidental spillage, wastewater effluent, and long-range transport. , Other studies have reported the measurement of 14 pesticides and their transformation products (TPs) in both surface water and drinking water. , The Luxembourg Water Management Agency (Administration de la Gestion de l’Eau, hereafter AGE), in compliance with the European Union Water Framework Directive (WFD), monitors different organic contaminants in Luxembourgish surface water . Among the 92 compounds included in the targeted analysis performed by AGE, five are pharmaceuticals: carbamazepine, diclofenac, ibuprofen, ketoprofen, and lidocaine, while the rest the targeted organic contaminants are pesticides and related compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Luxembourg has vineyards lining the Moselle River, agricultural activity in the north of the country, and a population largely centered in the capital, which together brings in a significant and varied chemical load into the environment. Previous studies have reported the presence of analgesics, antimicrobials, and estrogens in Luxembourgish surface water. Aside from providing data on the level of xenobiotics in Luxembourgish waters, these studies have also demonstrated that the presence of these chemicals is due to inputs from land use, accidental spillage, wastewater effluent, and long-range transport. , Other studies have reported the measurement of 14 pesticides and their transformation products (TPs) in both surface water and drinking water. , The Luxembourg Water Management Agency (Administration de la Gestion de l’Eau, hereafter AGE), in compliance with the European Union Water Framework Directive (WFD), monitors different organic contaminants in Luxembourgish surface water . Among the 92 compounds included in the targeted analysis performed by AGE, five are pharmaceuticals: carbamazepine, diclofenac, ibuprofen, ketoprofen, and lidocaine, while the rest the targeted organic contaminants are pesticides and related compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The following data-dependent (dd-)MS2 settings (in display order of instrumental acquisition method) were used: resolution (120,000 at m/z 200), automatic gain control (AGC) target (1.0×10 6 ), maximum injection time (IT): (70 ms), and scan range (m/z=60-900). For the selected ion monitoring dd-MS2/ddSIM the following were used: resolution (30,000 at m/z 200), AGC target (5.0×10 5 ), maximum IT (70 ms), loop count (5), Top N (5), isolation window (1.0 Da), (N)CE (30). Lastly, the following dd settings were used: minimum AGC target (8.0×10 3 ), intensity threshold (1.1×10 5 ), apex trigger (4-6 s), exclude isotopes (On), and dynamic exclusion (10.0 s).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Aside from providing data on the level of xenobiotics in Luxembourgish waters, these studies have also demonstrated that the presence of these chemicals are due to inputs from land use, accidental spillage, wastewater effluent, and long range transport. 1,[3][4][5][6] Other studies have reported the measurement of 14 pesticides and their transformation products (TPs) both in surface water and drinking water. 3,7 The Luxembourg Water Management Agency (Administration de la Gestion de l'Eau, hereafter AGE), in compliance with the European Union Water Framework Directive (WFD), monitors different organic contaminants in Luxembourgish surface water.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the previously reported presence of chemicals in Luxembourg's environment 2,[4][5][6][7] and the widespread use of chemicals in daily life, a large number of compounds could be considered as potential environmental pollutants in Luxembourg.…”
Section: Introductionmentioning
confidence: 99%